CAVLC codewords substitution for H.264/AVC video data hiding - Yih-Chuan Lin; I-Fong Hsu (Proceedings of IEEE International Symposium on Consumer Electronics, 2014)
This paper addresses the problem of hiding secret message in the bitstream of H.264/AVC compressed videos. Challenges behind the bitstream data-hiding problem are twofold: one is to maintain the drift error caused by the hiding process as minimum as possible, and the other is to keep the bit-rate unaffected after hiding the secret message. In the paper, a new codeword substitution approach is developed that employs the level-suffix codewords as the hiding domain to accommodate the secret message in the compressed bitstream. The proposed method guarantees the bit-rate of marked bitstream to be intact and makes the resultant drift error controllable by choosing suitable levelsuffix codewords for hiding data. Experimental results have shown that the proposed level-suffix codeword substitution approach exhibits good performance in terms of both hiding capacity and reconstructed visual quality.